Recent Progress of Ferroptosis in Lung Diseases - Yu, Shangjiang; Jia, Jinqiu; Zheng, Jinyu; Zhou, Yiyang; Jia, Danyun; Wang, Junlu (Frontiers in Cell and Developmental Biology, 2021)
Ferroptosis is a new form of programmed cell death due to iron-dependent excess accumulation of lipid peroxides and differs from other programmed cell deaths in morphological and biochemical characteristics. The process of ferroptosis is precisely regulated by iron metabolism, lipid metabolism, amino acid metabolism, and numerous signaling pathways, and plays a complex role in many pathophysiological processes. Recent studies have found that ferroptosis is closely associated with the development and progression of many lung diseases, including acute lung injury, pulmonary ischemia-reperfusion injury, lung cancer, chronic obstructive pulmonary disease, and pulmonary fibrosis. Here, we present a review of the main regulatory mechanisms of ferroptosis and its research progress in the pathogenesis and treatment of lung diseases, with the aim of providing new ideas for basic and clinical research of lung-related diseases.